Parvez Hasan. My Life, My Country: Memoirs of a Pakistani Economist. 2011. Lahore: Ferozsons (Pvt.) Ltd. 472 pages. Hard cover. $25.00. (The Pakistan Development Review, 2010)
This is a timely book. It comes out at an extraordinarily difficult time for the Pakistani economy. The country has seen many ups and downs in its turbulent history of 64 years. In the second half of the 1960s, many economists—some of them from the West1—saw Pakistan as a model of economic success which other developing nations could follow. Some scholars even viewed Ayub Khan’s political model as a success, able to address the problem the Nobel Prize winning economist Gunnar Myrdal had identified as the “soft Asian state”.2 Now, half a century later, the country is viewed as a highly troubled and stressed state.3 It faces numerous problems that could conceivably result in the collapse of the economy. Parvez Hasan’s book traces some of these ups and downs in Pakistan’s economic history. He presents them as a part of his life story.